Social cohesion and living conditions in the canadian arctic : from theory to measurement - Duhaime, Gérard; Searles, Edmund; Usher, Peter J.; Myers, Heather; Fréchette, Pierre (Kluwer Academic Publishers, 2024)
Social cohesion has emerged as a powerful hybrid concept used by academics and policy analysts. Academics use the concept to underline the social and economic failings of modernity, linking it to the decline of communal values and civic participation. Policy analysts use it to highlight the social and economic inequities caused by globalization. The desired effect of using this concept is often to influence governments to implement policies that will enhance social cohesion by reducing social and economic disparities. Despite its widespread use, however, statistical measures of social cohesion tend to overlook local, non-Western strategies of social inclusion as well as the social impact of non-Western economic systems, such as the mixed economy typical of many Aboriginal communities in North America. In this paper, we develop a model of social cohesion that addresses these omissions through the use of social indicators that measure both the behavior and perceptions of Inuit living in the Canadian Arctic with respect to the social, cultural and economic conditions of Arctic communities. We explain how and why measuring social cohesion is optimized by combining both culturally-specific and non-specific social indicators.